Komitmen manajemen, pengetahuan K3, perilaku K3, dan kecelakaan kerja pada perawat di RS PKU Muhammadiyah Yogyakarta - Anggit Pratiwi; Widodo Hariyono; Adi Heru Sutomo (Berita Kedokteran Masyarakat (BKM), 2016)
Management commitment, occupational safety and health knowledge and behavior, and work accidents among nurses in a private hospital in YogyakartaPurposeThis study aimed to determine the relationship between management commitment, knowledge and behavior of occupational safety and health on nursing work accidents in RS PKU Muhammadiyah. MethodsThis cross-sectional study involved 73 nurses as research subjects. Data were analyzed using simple and multiple linear regression tests. ResultsThere was a significant negative relationship between each variable of management commitment, safety and health knowledge, safety and health behavior, and occupational accidents. When analyzed collectively there was a strong relationship between management commitment, knowledge and behavior of occupational safety and health and occupational accidents. ConclusionThis study suggests that the management of PKU Muhammadiyah Yogyakarta hospital can maintain the results achieved in the prevention of occupational accidents, increase supervision of hazard factors that may occur in the workplace, incorporate aspects of occupational safety and health in each Standard Operating Procedure, and post written rules of occupational safety and health in each work area. Management is recommended to provide health and safety training to nurses and socialization of occupational safety and health on a regular basis.